Detrended fluctuation analysis can detect the impairment of heart rate regulation in patients with heart failure with preserved ejection fraction - Mizobuchi, Asako; Osawa, Kazuhiro; Tanaka, Masamichi; Yumoto, Akihisa; Saito, Hironori; Fuke, Soichiro (Journal of cardiology, 2021)
•Detrended fluctuation analysis was applied to heart failure patients.•Short-term heart rate regulation was impaired in preserved ejection fraction.•Short and long-term heart rate regulation was impaired in heart failure.•This approach may predict autonomic dysfunction in preserved ejection fraction. The impairment of short-term heart rate regulation in patients with heart failure with preserved ejection fraction (HFpEF) can cause acute hemodynamic collapse. Detrended fluctuation analysis (DFA) is a useful tool for the diagnosis of heart diseases and the prediction of mortality. In DFA, the short-term scaling exponent α is decreased in heart failure. However, its change in HFpEF patients remains unclear. Twenty patients diagnosed with HFpEF [defined as brain natriuretic peptide (BNP) >100 pg/mL, ejection fraction (EF) ≥50%, and without significant valvular disease], 20 diagnosed with non-HFpEF (BNP > 100 pg/mL and EF < 50%), and 20 control subjects generally matched for age and gender were enrolled. Holter electrocardiography was performed, and heart rate variability was calculated. In the DFA, the scaling exponents in 1000 beats were calculated for each 15-min segment and the average of all segments was used. We compared both the short-term (<11 beats, α1) and long-term (≥11 beats, α2) scaling exponents among the three groups. In the HFpEF, non-HFpEF, and control groups, α1 was 0.73 ± 0.27, 0.66 ± 0.29, and 1.01 ± 0.20 (p < 0.01), and α2 was 0.95 ± 0.08, 0.88 ± 0.11, and 0.96 ± 0.07 (p < 0.01), respectively. The α1 exponent was significantly decreased in the HFpEF group (p < 0.01 vs. control) and the non-HFpEF group (p < 0.01 vs. control), while the α2 exponent was significantly decreased in the non-HFpEF group only (p < 0.05 vs. HFpEF and control). Short-term heart rate regulation is impaired in patients with HFpEF, while patients with non-HFpEF have both short-term and long-term impairment.